Tilapia Skin Peptides Ameliorate Cyclophosphamide-Induced Anxiety- and Depression-Like Behavior via Improving Oxidative Stress, Neuroinflammation, Neuron Apoptosis, and Neurogenesis in Mice - Zhao, Yun-Tao; Yin, Haowen; Hu, Chuanyin; Zeng, Jian; Zhang, Shilin; Chen, Shaohong; Zheng, Wenjing; Li, Mengjiao; Jin, Leigang; Liu, You; Wu, Wenjin; Liu, Shucheng (Frontiers in Nutrition, 2022)
Anxiety- and depression-like behavior following chemotherapy treatment occurs in cancer patients with high probability and no specific therapeutics are available for treatment and prevention of this complication. Here, tilapia skin peptides (TSP), a novel enzymatically hydrolyzed bioactive peptide mixture, obtained from tilapia (Oreochromis mossambicus) scraps, were studied on cyclophosphamide (CP)-induced anxiety- and depression-like behavior in mice. Mice were received intraperitoneal injection of CP for 2 weeks, while TSP was administered for 4 weeks. After the end of the animal experiment, behavioral, biochemical, and molecular tests were carried out. The mice decreased preference for sugar water, increased immobility time in the forced swimming and tail suspension test, and decreased travel distance in the open field test in the Model group, compared with the Control group. Abnormal changes in behavioral tests were significantly improved after the TSP treatment. Additionally, abnormalities on superoxide dismutase, malondialdehyde, glutathione peroxidase were rescued by administration of 1000 mg/kg/d TSP in mice than that of the Model group. TSP has normalized the expression of Iba-1 and the levels of TNF-α and IL-1β in the hippocampus of mice, which indicated that TSP could observably ameliorate neuroinflammatory response in the hippocampus of mice. TSP ameliorated the apoptosis of hippocampal neurons of CA1 and CA3 regions in the TSP group versus the Model group. The number of doublecortin positive cells was drastically increased by administering 1000 mg/kg/d TSP in mice versus the Model group. Furthermore, TSP reversed the Nrf2/HO-1 signaling pathway, BDNF/TrkB/CREB signaling pathway, and reduced the Bcl-2/Bax/caspase-3 apoptosis pathway. In conclusion, TSP could restore CP-induced anxiety- and depression-like behavior via improving oxidative stress, neuroinflammation, neuron apoptosis, and neurogenesis in mice hippocampus.A